PERSONAL HYGIENE RELATIONSHIP AND ENVIRONMENTAL CLEANLINESS ON THE INCIDENCE OF SCABIES AT YAYASAN SUNAN KALIJAGA MALANG - Devy Putri Nursanti; Eri Puji Kumalasari; Anis Supriatin (Universitas STRADA Indonesia, 2024)
Scabies is an infectious disease caused by the parasite Sarcoptes scabiei which can dig tunnels in the skin and can cause itching. Scabies transmission can occur through direct contact or indirect contact. The purpose of this study was to determine the relationship between personal hygiene and environmental hygiene behavior towards the incidence of scabies in adolescents at the Yayasan Sunan Kalijaga Malang. The method used in this research is quantitative analytic observation with a cross sectional approach. Using the Simple Random Sampling technique, a sample of 70 respondents was obtained, the independent variable personal hygiene behavior and environmental hygiene used a questionnaire and the dependent variable the incidence of scabies used an observation sheet. Using the Chi-Square statistical test to determine the relationship between the two variables.